PENGARUH PEMBIASAAN SHOLAT DHUHA TERHADAP KECERDASAN EKSISTENSIAL - Riska Gani; Alfina Damayanti; Kasih Apriliana; Sri Indriani Harianja; Nyimas Muazzomi (STKIP Subang, 2024)
This research aims to develop existential intelligence through the practice of Duha prayer. Habit is also an activity that is carried out continuously to achieve a desired result. The method in this research uses the Systematic Literature Review (SLR) method by carrying out systematic and comprehensive literature evaluations on certain topics by collecting and analyzing all relevant data. The results of this research are that existential intelligence can be influenced by religious activities such as: Duha prayer, where getting used to Duha prayer can raise questions about existential intelligence. By implementing the practice of Duha prayers, it will have a good impact on children because through this, children will know that it is not only obligatory prayers that are carried out, but Duha prayers are also carried out even though they are sunnah.